Young and old adipocytes have differential influence on the development of osteoblasts. Issue 6 (November 2018) - Li, Wei; Wang, Cuizhe; Zhang, Meixiu; Wu, Jinxiu; Gu, Yajuan; Deng, Yuchun; Wang, Jingzhou; Zhang, Xueting; Feng, Jiale; Chen, Keru; Zhu, Jiaojiao; Xie, Jianxin; et al.
Abstract: Objective: The aim of the current study was to investigate the effect of adipocytes on the differentiation of osteoblasts at different stages of adipocyte development. Methods: BMSCs were isolated from 4-week-old male wistar rat femurs and tibias, and flow cytometry was performed. Adipocytes were derived from BMSCs, cell morphology was continually observed from day 21 to day 50. Adipocyte medium was collected once every 2 days (d) and ELISA kits were used for detection of triglycerides (TG), tumor necrosis factor-α (TNF-α), and interleukin-6(IL-6) expression level. 21 d and 40 d old adipocyte and osteoblast cells were co-cultured, and alizarin red staining was performed after 21 d. After co-culture, the adherent cells were collected, and the expression of receptor activator of nuclear factor kappa-B ligand (RANKL) and osteoprotegerin (OPG) was detected by real time PCR. Result: Results of cell characterisation showed that the cells had positive expression of CD29 (97.92%) and CD44 (89.32%). With the increase of the induction time of mature adipocytes, the number of adipocyte on 21th d was significantly higher than 40th d, while the volume of adipocyte was significantly lower than 40th d (P < 0.05). The levels of TG(2.6 ± 0.83 mmol/l VS 3.8 ± 0.66 mmol/l), TNF-α(30.5 ± 2.53 pg/ml VS 57.6 ± 5.1 pg/ml), and IL-6(32.5 ± 1.42 pg/ml VS 55.1 ± 5.97 pg/ml) secreted by adipocytes increased with induction time: 40th d was significantly higher than 21th d (P < 0.01). When 21th d adipocytes and osteoblasts were co-cultured, the number of calcium nodules significantly increased over that of the positive control group, When 40th d adipocytes and osteoblasts were co-cultured, the number of calcium nodules significantly decreased over that of the positive control group (P < 0.05). The OPG(68.9 ± 5.39 VS 1.00 ± 0.36) expression was significantly increased, and the expression of RANKL (2.0 ± 0.84 VS 34.4 ± 2.01) was significantly decreased from the 21th d adipocytes co-cultured group compared with the 40th d adipocytes co-cultured group (P < 0.001). Conclusion: The differential size of adipocytes in the bone marrow can affect bone metabolism by regulating the expression of OPG/RANKL.